Small towns, vast urban problems: the reality of São Sebastião da Amoreira, Brazil - Fernandes, Pedro Henrique Carnevalli (2018)
Urban problems exist since when the first capitalist cities appeared, especially because of its unfairness. For this reason, one of the main objectives of this research is show the Brazilian small towns has similar or even bigger problems than big cities, since they are in the same model of urbanization. Thus, this research demystify the perspective of small towns like spaces without urban problems and that only major centers have absence of health services, education, income generation, security, among others problems. The study happens at a small town called São Sebastião da Amoreira, located in the hinterland of Paraná’s State. The survey brings the main urban problems of the city, pointed out by local inhabitants, history and by demographic and socials indicators. For this, have been used these research methods: bibliographic and date survey, application of questionnaires with city’s population, descriptive researches and photographic records about the essential urban problems. The intense carelessness with the city resulted in many urban problems and the most considered by society were: health services, asphaltic infrastructure and absence of creation of jobs. Therefore, it is concluded that population give up of reside in the city that has been facing a demographic emptying.